Structure and Activity of a New Low‐Molecular‐Weight Heparin Produced by Enzymatic Ultrafiltration. Issue 5 (14th March 2014) - Fu, Li; Zhang, Fuming; Li, Guoyun; Onishi, Akihiro; Bhaskar, Ujjwal; Sun, Peilong; Linhardt, Robert J.
<x xml:space="preserve">Abstract</x> The standard process for preparing the low‐molecular‐weight heparin (LMWH) tinzaparin, through the partial enzymatic depolymerization of heparin, results in a reduced yield because of the formation of a high content of undesired disaccharides and tetrasaccharides. An enzymatic ultrafiltration reactor for LMWH preparation was developed to overcome this problem. The behavior, of the heparin oligosaccharides and polysaccharides using various membranes and conditions, was investigated to optimize this reactor. A novel product, LMWH‐II, was produced from the controlled depolymerization of heparin using heparin lyase II in this optimized ultrafiltration reactor. Enzymatic ultrafiltration provides easy control and high yields (>80%) of LMWH‐II. The molecular weight properties of LMWH‐II were similar to other commercial LMWHs. The structure of LMWH‐II closely matched heparin's core structural features. Most of the common process artifacts, present in many commercial LWMHs, were eliminated as demonstrated by 1D and 2D nuclear magnetic resonance spectroscopy. The antithrombin III and platelet factor‐4 binding affinity of LMWH‐II were comparable to commercial LMWHs, as was its in vitro anticoagulant activity. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1375–1383, 2014